Pelatihan Implementasi Pemasaran Melalui E-commerce Pada UMKM Toto Kompos - Abdulah, Budiman; Ruseno, Ndaru; Sandopart, Dewa Putu Yohanes Yohanes Agata L.; Santoso, Imam; Andrianto, Usman; Suryaningsih, Fina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this community service is to improve the weakness of product marketing, through training and mentoring activities for E-Commerce marketing management. Training methods with socialization, material presentation, evaluation and revision of activities. The results of the activity participants were able to master and implement their products in E-Commerce marketing. The conclusion is that MSMEs need to maximize the potential of E-Commerce marketing to be used as a means of promotion and increasing their business.